The world of the rebels of 1857 : proclamations, tracts and documents, 1857-1859 - Iqbal Hussain (Primus, 2019)
In the 'rebel world' of 1857, indigenous discourse on the great uprising in the form of proclamations, pamphlets and appeals issued by rebel leaders and other ideologues offers primary data for understanding the motives of the rebels, their means of mobilization and the people who were sought to be mobilized. .